Mind the gap: Identifying training needs of community health workers to address mental health in U.S. Latino communities during and beyond the COVID-19 pandemic - Garcini, Luz M.; Kanzler, Kathryn E.; Daly, Ryan; Abraham, Cristina; Hernandez, Ludivina; Romero, Raquel; Rosenfeld, Jason (Frontiers in Public Health, 2022)
Addressing mental health is an important part of the COVID-19 response among historically underserved communities, which have been disproportionately affected. Community Health Workers (CHWs) are well placed to offer insights about barriers to mental health service use in their communities, and they are well positioned to address mental health gaps by providing education, resources, and assistance to bridging the gap for the use of more traditional mental health services. Using the perspectives of CHWs, this project identified barriers faced by CHWs in assisting community members with their mental health needs, along with relevant training needs to more effectively deliver mental health resources, referrals, and recommendations to community members. Survey data along with data from focus groups were collected among 43 CHWs in communities that have been historically underserved near the U.S.-Mexico border region. Quantitative data were analyzed using descriptive statistics whereas qualitative data were analyzed through systematic methods. Identified barriers to assisting community members with their mental health needs exist at the personal, community, environmental and organizational levels, and ranged from fear and mistrust to limited services, resources, funding and training opportunities. To help address the aforementioned barriers and facilitate access to mental health service use in their communities, CHWs identified and described opportunities for training in core areas including communication, mental illness symptom identification, trauma, self-care and stress reduction, and cultural awareness and sensitivity. Needs-based training programs that incorporate the insights of CHWs are a crucial part of promoting community-based mental health to address existing mental health disparities in access to and use of mental health services.